Reliability of an in-water repeated-sprint test for water polo - Tan, F. H. Y.; Polglaze, T.; Dawson, B. (International Journal of Sports Physiology and Performance, 2010)
Time-motion studies indicate the importance of repeated high-intensity activities during water polo match play. The purpose of this study was to assess the reliability of an in-water repeated-sprint test, which comprised 6 × 10-m all-out sprints, departing every 17 s. This protocol was chosen to replicate the regular intense periods of match play.